Export subsidies in a heterogeneous firms framework - Christian Helmers; Natalia Trofimenko (Kiel Institute for the World Economy (IfW), 2009)
We evaluate the impact of firm-specific export subsidies on exports in Colombia. Using a two-stage Heckman selection procedure, we obtain firm-specific predicted subsidy amounts that can be explained by the characteristics that determine the firms' eligibility for the government support and its amount. Drawing on the accounts of the discretionary allocation of subsidies in developing countries, we regard the discrepancy between the predicted and the observed subsidy amounts as a proxy for the firm's ties to government officials. Controlling for observable and unobservable firm characteristics and persistence in exports, we find that although, in general, subsidies exhibit positive impact on export volumes, this impact is diminishing in subsidy size and in the degree of firm's connectedness to government officials.
Keywords: F10; F13; L20; H20; 330; Export subsidies; exports; Heckman selection; System GMM; Exportsubvention; Wirtschaftspolitische Wirkungsanalyse; Export; Mikroökonometrie; Schätzung; Momentenmethode; Schätzung; Kolumbien